Utilization of Paku Uban (Nephrolepis biserrata) Extract as a Molting Stimulant of Mud Crabs (Scylla spp.) in Traditional Ponds - Diana Maulianawati; Rukisah Rukisah; Awaludin Awaludin; Muhammad Iswan Guntur (Jurnal Ilmiah Perikanan dan Kelautan)
Highlights • The Paku Uban (Nephrolepis biserrata) was identified and analyzed • The ability of paku uban to stimulated molting process of Scylla sp was analyzed • The paku uban (Nephrolepis biserrata) could increase the presentation of molting and accelerate molting process